Invent, reinvent, thrive the keys to success for any start-up, entrepreneur, or family business - Shefsky, Lloyd E., author (McGraw-Hill Education, 2014)
Build your own business using the same methods that launched Starbucks, Staples, and others to the top of the food chain Invent, Reinvent, Thrive reveals the common thread that consistently leads to entrepreneurial success: Reinvention. It explains not just how to reinvent concepts and ideas from the start, but how to continuously innovate and reinvent one's business to meet constantly changing conditions in the marketplace. The author provides best practices from his professional experience, case studies, and original interviews to show where new business owners are falling short or missing incredible opportunities; where they fail to take risks or innovate; and how they can positively rework, revitalize, and reinvent themselves and their businesses. Shefksy also provides insight into family businesses and the unique challenges they face. Includes original interviews with Howard Schultz (Chairman and CEO of Starbucks), Tom Stemberg (founder of Staples), Maxine Clark (CEO of Build-A-Bear Workshop), Marilyn Carlson Nelson (Chairman and CEO of Carlson Companies), and other high-profile figures Lloyd Shefsky is a Clinical Professor of Entrepreneurship, founder and Co-Director of the Kellog Center for Family Enterprises, and the co-founder of the Center for Executive Women at the Kellogg School of Management